2004
DOI: 10.1097/00061198-200408000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Response of Retinal Vessel Diameters to Flicker Stimulation in Patients with Early Open Angle Glaucoma

Abstract: Flicker-induced vasodilatation of retinal veins is significantly diminished in patients with glaucoma compared with healthy volunteers. This indicates that regulation of retinal vascular tone is impaired in patients with early glaucoma, independently of antiglaucoma medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 16 publications
7
91
1
5
Order By: Relevance
“…117 Also, in the early stages of the disease, a reduction in flicker-evoked dilation of retinal venules but not arterioles is observed in patients. 118 These observations support the hypothesis that the pathologic changes associated with glaucoma may be due, at least in some instances, to retinal ischemia caused by the increase in intraocular pressure and the resulting decrease in perfusion pressure, leading to a decrease in retinal blood flow. 119 It should be noted, however, that glaucoma can develop in patients with normal intraocular pressure.…”
Section: Modulation Of Functional Hyperemia In the Retina Oxygen Modusupporting
confidence: 81%
“…117 Also, in the early stages of the disease, a reduction in flicker-evoked dilation of retinal venules but not arterioles is observed in patients. 118 These observations support the hypothesis that the pathologic changes associated with glaucoma may be due, at least in some instances, to retinal ischemia caused by the increase in intraocular pressure and the resulting decrease in perfusion pressure, leading to a decrease in retinal blood flow. 119 It should be noted, however, that glaucoma can develop in patients with normal intraocular pressure.…”
Section: Modulation Of Functional Hyperemia In the Retina Oxygen Modusupporting
confidence: 81%
“…192 Indeed, neurovascular coupling in the retina appears to be disturbed early in glaucoma. 190,193,194 In principle, restoration of neurovascular coupling may be an attractive approach for glaucoma, but the mechanisms that lead to its breakdown are poorly understood.…”
Section: Other Approachesmentioning
confidence: 99%
“…Previous clinical studies using the DVA have shown the impaired dilation to this flicker, reflecting possibly endothelial dysfunction, is associated with systemic diseases, 13 including hypertension 8 and diabetes, 14 and ocular diseases, such as diabetic retinopathy 14 and glaucoma. 15 However, although DVA has previously been shown to be reproducible in whites, 16 there have been no similar data in groups/races other than whites, including Asians. In this study, we aim to assess the reproducibility of the retinal vessel dilation in response to flicker-light, as measured by the DVA in Asians and compare the corresponding reproducibility reported in whites.…”
Section: Introductionmentioning
confidence: 97%